2014
DOI: 10.1039/c3ee43754j
|View full text |Cite
|
Sign up to set email alerts
|

Wiring zinc in three dimensions re-writes battery performance—dendrite-free cycling

Abstract: Zinc-based replacements for Li-ion batteries are now feasible by using 3D-interconnected Zn sponges that suppress dendrite formation when cycled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
358
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(371 citation statements)
references
References 40 publications
(37 reference statements)
8
358
1
2
Order By: Relevance
“…The high utilization of the hyper-dendritic nanoporous zinc foam showed great rate capability and was comparable to results of conventional zinc anodes in a sponge form-factor. 13,33 Conventional zinc anodes usually consist of active material, additives to suppress hydrogen and control the morphological uniformity of zinc deposition, and polymeric binders to keep zinc particles intact. 1,23,27,34 In this work, the zinc foam was prepared, in situ, by reducing zincate ions on a current collector with no other necessary compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high utilization of the hyper-dendritic nanoporous zinc foam showed great rate capability and was comparable to results of conventional zinc anodes in a sponge form-factor. 13,33 Conventional zinc anodes usually consist of active material, additives to suppress hydrogen and control the morphological uniformity of zinc deposition, and polymeric binders to keep zinc particles intact. 1,23,27,34 In this work, the zinc foam was prepared, in situ, by reducing zincate ions on a current collector with no other necessary compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has indicated that zinc structures with submicron features can undergo 50 charge-discharge cycles without failure. 13 Here, we describe a simple mechanism for making such structures, with the option to alter the surface kinetics as a function of process regime.…”
Section: Introductionmentioning
confidence: 99%
“…z E-mail: steingart@princeton.edu Recently, several three-dimensional zinc foam structures have been suggested to provide cyclable zinc electrodes without the problems associated with dendrite growth and morphology changes. 5,12 In addition to providing high utilization under primary discharge, these electrode structures also allow for significant improvements in cyclability, albeit at the loss of volumetric energy density. Co-deposition of nano-zinc/graphene composites have also been demonstrated, with potentially useful applications in energy storage.…”
mentioning
confidence: 99%
“…5,12 In addition to providing high utilization under primary discharge, these electrode structures also allow for significant improvements in cyclability, albeit at the loss of volumetric energy density. Co-deposition of nano-zinc/graphene composites have also been demonstrated, with potentially useful applications in energy storage.…”
mentioning
confidence: 99%
See 1 more Smart Citation